Synthesis of Phenyl‐1‐benzoxepinols Isolated from Butcher's Broom and Analogous Benzoxepines. Issue 15 (8th April 2014) - Herrmann, Josef M.; Untergehrer, Monika; Jürgenliemk, Guido; Heilmann, Jörg; König, Burkhard
Abstract: Extracts of Ruscus aculeatus L., known as butcher's broom, are mainly used for the treatment of chronic venous insufficiency (CVI). In a recent study on the phenolic compounds of Rusci rhizoma, new phenyl‐1‐benzoxepinols were isolated. As the therapeutic effect of butcher's broom is ascribed to the pharmacological activity of the main constituents, steroidal saponins and their aglycones the ruscogenins, the role of the newly identified compounds was of interest. Owing to the low availability of the compounds by isolation, we synthesized them for pharmacological testing. In an ORAC–fluorescein assay they revealed a significant antioxidative activity, which may contribute to the anti‐inflammatory properties of the phenolic fraction obtained from Rusci rhizoma extracts. Abstract : Butcher's broom extracts are used to treat inflammation. The physiological activity is mainly ascribed to steroidal saponins, but recently identified phenolic compounds, ruscozepines, may also contribute. Ruscozepine A and B and several derivatives were prepared by racemic synthesis and an ORAC–fluorescein (ORAC = oxygen radical absorbance capacity) assay revealed their antioxidative properties.